Optical sensor for surface plasmon resonance spectroscopy - Mat Yunus, Wan Mahmood; Yap, Wing Fen; Talib, Zainal Abidin (2012)
The present invention relates to an optical sensor for surface plasmon resonance spectroscopy detection of a heavy metal ion, comprising a sensor layer (21) deposited on a metal layer (20); characterized in that said sensor layer (21) comprises p-tert-butylcalix[4]arene-tetrakis (BCAT) immobilized in a polymer-based thin film. There is also provided a method for producing an optical sensor for surface plasmon resonance spectroscopy detection of a heavy metal ion comprising the steps of: mixing p-tert-butylcalix[4]arene-tetrakis (BCAT) solution with a polymer solution to form a mixture; then depositing the mixture on a metal layer (20) to form a sensor layer (21), comprising a polymer-based thin film with immobilized p-tert-butylcalix[4]arene-tetrakis (BCAT), on said metal layer (20). There is also described a method for surface plasmon resonance spectroscopy detection of a heavy metal ion in an analyte, using said sensor layer (21) comprising p-tert-butylcalix[4]arene-tetrakis (BCAT) immobilized in a polymer-based thin film.